Предмет:
МатематикаАвтор:
анонимРешим квадратное уравнение x2 + 10 * x – 24 = 0.
D = b2 – 4 * a * c = 102 – 4 * 1 * (-24) = 100 + 96 = 196.
Х1 = (-10 – √196) / (2·1) = -10 – 14 / 2 = -24 / 2 = -12.
Х2 = (-10 + √196) / (2·1) = -10 + 14 / 2 = 4 / 2 = 2.
Тогда:
Х2 + 10 * Х – 24 = (Х – (-12)) * (Х – 2) = (Х + 12) * (Х – 2).
Ответ: Х2 + 10 * Х – 24 = (Х + 12) * (Х – 2).
Автор:
tamaraДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть